Dinamika Hubungan Sponsorship dalam Narcotics Anonymous (NA) sebagai Strategi Pemulihan Adiksi Narkoba - Lilik Mudloyati Choiriyah; Lifina Dewi Pohan (Fakultas Psikologi, Universitas Putra Indonesia YPTK Padang, 2023)
Indonesia still has a fairly high rate of drug abuse. Some limitations in drug management strategies in Indonesia, such as obstacles to intervention in prisons and lack of involvement in recovery from addicts, can be overcome by the existence of alternative drug treatment strategies. One of the recommended rehabilitation methods is sponsorship from Narcotics Anonymous. This method allows the involvement of the addict in the recovery process from drug addiction and can trigger the desire of the addict to continue the recovery process with social support provided through sponsorship relationships. This study aims to understand the dynamics of the experiences of individuals undergoing sponsorship in the Narcotics Anonymous community for drug addiction recovery. A single case study with an in-depth interview method was conducted on 42-year-old individuals undergoing drug recovery, as well as having experience participating in Narcotics Anonymous and having sponsorship relationships, both as sponsors and sponsors. In-depth interviews referred to four themes emerging from participants' experiences: (1) the main problem of addiction is behavior that forms with drug use, (2) opening the ears and expressing the heart can have therapeutic effects during recovery, (3) learning from sponsors during recovery, and (4) sharing experiences as sponsors is a form of recovery. The results of the study found that the dynamics of sponsorship relationships in NA become a social support that has therapeutic value for its members, facilitates abstinence, and raises positive expectations in recovery. As sponsors, participants who provide support also find it helpful in undergoing recovery through helper therapy principles. It can be said that the sponsorship relationship as one of the social supports in drug handling is felt to provide many benefits and can effectively help the recovery process of drug addiction so that it can be considered for mental health practitioners as an alternative therapy in handling drug addiction.